Divisão Técnica Acadêmica - Kawagoe, Marina Midori Sakamoto; Reatto, Diogo; Rocha, Maria de Fátima Sousa da; Yonemoto, Marie Nishigima; Leal, Adriana de Paula e Silva Rahal; Zagatto, Valéria de Queiroz Marcondes; Mada, Lilian Sayuri; Matos, Cristiane Regina Lui; Patim, Samuel Aparecido; Oliveira, Renato Gomes de; Tutumi, Maurício Hiromi; Silva, Patrick Santos Nogueira da; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Marina Midori Sakamoto Kawagoe Diogo Reatto Maria de Fátima Sousa da Rocha Marie Nishigima Yonemoto Adriana de Paula e Silva Rahal Leal Samuel Aparecido Patim